Management Information System of the Billing Subsystem: A Prototype Design - Farida Setianingsih; Adhistya Erna Permanasari; Warsun Najib (IJITEE (International Journal of Information Technology and Electrical Engineering), 2019)
Abstract— Prof. Soeparwi Veterinary Hospital is one of veterinary medical service providers in Yogyakarta ad Central Java areas in which the transaction and the documentation managing process is still done manually. Therefore, Prof. Soeparwi VH needs a management information system that facilitate them in managing process and documentation of transactions, one of which is through billing or billing subsystem. This subsystem was designed using UML and was developed in a form of web-based prototype using PHP and HTML languages as well as CSS with CodeIgniter framework and MySQL for database.  The development of this billing subsystem applied a Rapid Application Development (RAD) model process that focused on the working model and obtained feedback from users to improve the system. Results of this system's development were evaluated with a system feasibility test and functionality test. A system feasibility test was administered by distributing Likert scale questionnaire and analysed them based on a summated rating scale method which showed a result of 85.4%. That result indicates that users strongly agree that the system has met their needs.  The system functionality was tested using a black box method and the result was that the system properly functioned. This billing subsystem could process transaction bills automatically included in the calculation. This system produced bills and reports that could be printed and exported. In addition, data was stored in a database so that it supported paperless documentation.